2005
DOI: 10.1158/1078-0432.ccr-05-0040
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Responsive Finger Protein as a New Potential Biomarker for Breast Cancer

Abstract: Purpose: Estrogen-responsive finger protein (Efp) is a member of RING finger-B box-Coiled Coil family and is also a downstream target of estrogen receptor a. Previously, Efp was shown to mediate estrogen-induced cell growth, which suggests possible involvement in the development of human breast carcinomas. In this study, we examined expression of Efp in breast carcinoma tissues and correlated these findings with various clinicopathologic variables. Experimental Design: Thirty frozen specimens of breast carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 20 publications
3
45
0
Order By: Relevance
“…In some cases, this upregulation was associated with enhanced metastatic capacity as well as with poor patient prognosis (Bektas et al, 2008) In contrast, Ube1L is often lost or downregulated in lung cancer, indicating a tumorsuppressor function of Ube1L in this tissue (Pitterle et al, 1998). The EFP expression is increased in advanced breast tumors and positively correlates with a poor prognosis (Sakuma et al, 2005;Suzuki et al, 2005), which seems to be tightly connected to the specific function of EFP in the regulation of ER activity. As these distinct dysregulated expression patterns of the ISGylation system may reflect the tissue-specific functions of the components, an upregulation of ISG15, UbcH8, EFP and Herc5 in PCa is probably associated with a tissue-specific function of the ISGylation system in AR regulation.…”
Section: Discussionmentioning
confidence: 95%
“…In some cases, this upregulation was associated with enhanced metastatic capacity as well as with poor patient prognosis (Bektas et al, 2008) In contrast, Ube1L is often lost or downregulated in lung cancer, indicating a tumorsuppressor function of Ube1L in this tissue (Pitterle et al, 1998). The EFP expression is increased in advanced breast tumors and positively correlates with a poor prognosis (Sakuma et al, 2005;Suzuki et al, 2005), which seems to be tightly connected to the specific function of EFP in the regulation of ER activity. As these distinct dysregulated expression patterns of the ISGylation system may reflect the tissue-specific functions of the components, an upregulation of ISG15, UbcH8, EFP and Herc5 in PCa is probably associated with a tissue-specific function of the ISGylation system in AR regulation.…”
Section: Discussionmentioning
confidence: 95%
“…9 EFP mRNA and protein were reported to be overexpressed and significantly correlated with poor prognosis of breast cancer patients. 10 WW domain-containing protein 1 (WWP1) is an HECT (homologous to the E6-associated protein carboxyl terminus) domain-containing E3 ubiquitin ligase. Growing evidence suggests that WWP1 negatively regulates the TGF-b tumor suppressor pathway by mediating the ubiquitination and degradation of TGFb receptor 1 (TbR1), 11 Smad2 12 and Smad4.…”
mentioning
confidence: 99%
“…Further, Efp has been identified as an independent prognostic factor for breast cancer, regardless of ERa status. 7 Therefore, we expect that if Efp is expressed, siEfp-1 and chimeric siEfp will be used as new therapeutic tools for breast cancer treatment regardless of ERa status and can be used to treat patients with endocrine-resistant or relapsed tumors.…”
Section: Discussionmentioning
confidence: 99%
“…4 Clinicopathological studies on breast cancer patients have revealed that Efp immunoreactivity was positively associated with the lymph node status or ERa status and negatively correlated with histological grade. 7 Multivariate analyses of disease-free survival and overall survival of breast cancer patients have revealed that Efp immunoreactivity is correlated with poor prognosis and is an independent marker of breast cancer. 7 Moreover, we showed that Efp promotes the growth of breast tumors by functioning as a ubiquitin E3 ligase that targets the G2/M cell-cycle checkpoint 14-3-3s.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation